2012
DOI: 10.1021/ic300799e
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Hydrotalcites: The Addition of Highly Electronegative Species in Layered Double Hydroxides To Tune Basicity

Abstract: Hydrotalcite-like compounds were synthesized by coprecipitation using a constant-pH method. Aluminum was introduced in the form of an octahedral aluminum fluorine complex during the synthesis. Controlling the pH during the synthesis ensured that aluminum fluorine did not decompose to tetrahedral species but remained in the octahedral (AlF(6))(3-) form to be incorporated into brucite-like sheets. The physicochemical, thermal, and spectroscopic characterizations showed significant modifications by fluorine intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
(54 reference statements)
1
34
1
Order By: Relevance
“…The first step of thermal decomposition of HTlcs at 373-473 K included two overlapped peaks, which can be assigned to the elimination of physically adsorbed water and the remove of the interlayer water molecules. It can be seen that the introduction of (AlF 6 ) 3À into the HTl structures increased the temperature of interlayer water loss, because fluorine can increase the strength of hydrogen bonds with hydrogen atoms from water [26]. Subsequently, the second weight loss at 473-623 K may ascribed to the removal of both the hydroxyl groups from the HTl network and carbonate anions from the interlayer anion, resulting in the collapse of the layered structure [33].…”
Section: Textural and Structural Properties Of The Prepared Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first step of thermal decomposition of HTlcs at 373-473 K included two overlapped peaks, which can be assigned to the elimination of physically adsorbed water and the remove of the interlayer water molecules. It can be seen that the introduction of (AlF 6 ) 3À into the HTl structures increased the temperature of interlayer water loss, because fluorine can increase the strength of hydrogen bonds with hydrogen atoms from water [26]. Subsequently, the second weight loss at 473-623 K may ascribed to the removal of both the hydroxyl groups from the HTl network and carbonate anions from the interlayer anion, resulting in the collapse of the layered structure [33].…”
Section: Textural and Structural Properties Of The Prepared Materialsmentioning
confidence: 99%
“…These results were related to the stability of (AlF 6 ) 3À species in solution. There exists an ionic equilibrium between (AlF 6 ) 3À and (AlF 4 ) À in aqueous aluminumsodium fluoride mixtures and only (AlF 6 ) 3À can react to be incorporated to hydrotalcite-like (HTl) structure under alkaline conditions as those used in a coprecipitation synthesis of hydrotalcite-like compounds (HTlcs) [26]. To accomplish the LeChatelier's principle, (AlF 6 ) 3À species were produced continuously during the synthesis.…”
Section: Textural and Structural Properties Of The Prepared Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Now, coming back to chemical shift at À182 ppm, it is closer to À190 ppm and it should be concluded that enriched fluorine AlF 6Àx O x species are formed. The fluorination of mixed oxide Mg(Al)O emerged from the thermal treatment of LDH was reported, but a better distribution of fluorine was obtained because of the method used by Lima et al [40]. In our case, the impregnation seems to be more local avoiding a high dispersion of fluorine into the structure of mixed oxide.…”
Section: Nitrogen Physisorptionmentioning
confidence: 53%